Kharif onion makes farmers cheerful - Kumar, Rakesh; Singh, Ritu (Indian Horticulture, 2019)
Some farmers in south-west Delhi take advantage of higher price in market. The KVK, Uiwa, is trying to popularize cultivation of onion in kharif season in Nazafgarh district. Kuldeep Singh Yadav, of village Jafferpur, kalan (Najafgarh) New Delhi, received maximum return from kharif onion cultivation. He sold onion bulbs and green leaves for â‚¹25,000, earning a total of â‚¹38,000 as a net return from an acre of land.